DESIGN AND APPLICATION OF AC/DC SWITCHING POWER SUPPLY WITH HALF BRIDGE DC/DC CONVERTER TOPOLOGY FOR BATTERY SYSTEMS of ELECTRICAL VEHICLE - AKGÜL, Celaletdin; ÇETİNCEVİZ, Yücel; ŞEHİRLİ, Erdal (Kütahya Dumlupinar Üniversitesi, 2023)
This study presents design, analysis and application details of electrical vehicle battery charge device based on half bridge DC-DC converter. Half bridge DC-DC converter in the paper has 620 W power, 25 kHz switching frequency and input DC voltage is obtained by uncontrolled bridge rectifier. In addition, information about the battery that is charged, and battery pack are given. Besides, a protection structure of battery is added by measuring both current and voltage of battery. Firstly, equations required for half bridge DC-DC converter is derived and simulation of battery charge circuit is realized by using PSIM and MATLAB/Simulink. Then, the results of the experimental study and the simulation results are given comparatively. The experimental results prove the accuracy of the simulation studies.
Keywords: Engineering; Application; Half Bridge DC/DC Converter; Electrical Vehicle; Battery; MATLAB/Simulink; Application; Half Bridge DC-DC Converter; Mühendislik; Battery; Electrical Vehicle; MATLAB/Simulink; 7. Clean energy